Model Pelayanan Terpadu Berbasis Kearifan Lokal: Kajian Penggabungan Pelayanan Adat Dan Administrasi Di Desa Ngadisari - Maksin, Mastina; Septiandika, Verto; Dewi, Renny Candra; Yudianto, Eko; Syamsya Q, Mareta (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The provision of public services is currently still one of the public's assessments of the government. Local wisdom values ​​in local communities are often neglected, so the government needs to make observations regarding service models so that they do not abandon traditional values ​​and local wisdom. This research focuses on studying the combination of traditional and administrative service models in Ngadisari village. This research is descriptive qualitative in nature using interview techniques with sources who were chosen deliberately and who are considered to understand the things that will be studied in this paper. The results of this research indicate that the collaboration of traditional and administrative services in Ngadisari Village based on local wisdom is running optimally, both in verbal, written and action services. This is of course adjusted to the respective duties of both the village government and traditional stakeholders as actors in traditional services. Communication between the village government and traditional stakeholders is the key to the success of the integrated service model in Ngadisari Village so that services remain good and of high quality.